Studies in archaeological conservation - Caple, Chris, 1958-; Garlick, Vicky (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Studies in Archaeological Conservation features a range of case studies that explore the techniques and approaches used in current conservation practice around the world and, taken together, provide a picture of present practice in some of the world-leading museums and heritage organisations. Archaeological excavations produce thousands of corroded and degraded fragments of metal, ceramic, and organic material that are transformed by archaeological conservators into the beautiful and informative objects that fill the cases of museums. The knowledge and expertise required to undertake this transformation is demonstrated within this book in a series of 26 fascinating case studies in archaeological conservation and artefact investigation, undertaken in laboratories around the world. These case studies are contextualised by a detailed introductory chapter, which explores the challenges presented by researching and conserving archaeological artefacts and details how the case studies illustrate the current state of the subject. Studies in Archaeological Conservation is the first book for over a quarter of a century to show the range and diversity of archaeological conservation, in this case through a series of case studies. As a result, the book will be of great interest to practising conservators, conservation students, and archaeologists around the world.
PART I: Introduction -- 1. Introduction: the challenges of archaeological conservation -- PART II: Case studies: stone and plaster -- 2. The conservation of a Viking Age sculpture from York -- 3. A plaster cast of a Mesopotamian lioness in the Durham Oriental Museum -- 4. The conservation of an Egyptian rock crystal dish -- 5. The conservation of a fossil suffering from pyrite decay -- PART III: Ceramics and glass -- 6. Retreatment of an archaeological glass beaker -- 7. Pierced Bronze Age ceramic vessel from Jericho -- 8. Conservation of a late Parthian-early Sasanian vessel -- 9. Conservation of an Archaic cuneiform tablet from Babylonia -- 10. Boat model masthead in faience -- PART IV: Metals -- 11. Copper alloy objects suspected of bronze disease: the Burrell Bronzes -- 12. Economy and decision making in the use of benzotriazole -- 13. Button from the River Wear, Durham -- 14. Cleaning, consolidating, and reassembling a fragmentary copper alloy object -- 15. A late-medieval pectoral cross pilgrim sign from the River Wear, Durham -- 16. Conservation of a pewter dish from the wreck of The Coronation -- 17. The conservation of threeth-century archaeological iron keys -- PART V: Organics - wood, textiles, leather -- 18. Interventive conservation of a waterlogged wooden bucket -- 19. Re-treatment of a marine archaeological leather shoe -- 20. The conservation ofMesolithic birch bark rolls from Star Carr -- 21. Investigation of a charred wooden torso from Uruk -- 22. Restorage of archaeological textiles at the Museum of London -- 23. Conservation and repackaging of a collection of Coptic textiles -- PART VI: Bone, composite and display -- 24. Conservation project: the Stengade double grave, Langeland Museum, Denmark -- 25. Conservation of two World War I rifles and a military equipment belt -- 26. Conservation of a Roman skeleton -- 27. Treatment of a block-lifted chicken skeleton
OCLC-licensed vendor bibliographic record.
Keywords: Archaeology -- Methodology -- Case studies; Historic sites -- Conservation and restoration -- Case studies; SOCIAL SCIENCE / Archaeology